Skull-photo superimposition: The state of the art in Malaysia and its legal significance / Hetty Susilawati Asmuni - Hetty Susilawati, Asmuni (2008)
The utility of the so-called skull-photo superimposition has been well established in many parts of a country, for example India, Australia, and New Zealand. The admissibility of the technique as an evidence was recognized and accepted in their court of law. Skull-photo superimposition is a technique whereby an unknown skull is superimposed or laid on the photograph of a suspected dead person in an attempt to make identification by appreciating and analyzing the match between the two. Skull-photo superimposition is a supplementary technique and used to establish identification of dead bodies. The present study aimed to investigate the utility of skull-photo superimposition technique in Malaysia and the admissibility of the skull-photo evidence in court. From the research findings, skull-photo superimposition technique was not much progressing in Malaysia.